Thermal Preferences and Critical Temperature Regimes of the Western North Atlantic Invasive Lionfish Complex (Pterois spp.) - Barker, Benjamin (NSUWorks, 2015)
Temperature preference, behavioral tolerance, and physiological tolerances were determined for locally captured, invasive juvenile lionfish at four different acclimation temperatures (13°C, 20°C, 25 °C and 32°C). Temperature preferences and avoidance temperatures were evaluated using an automated shuttlebox system that presents subject-driven temperature stimuli to subjects, who control the temperature with their movement throughout the tank for 12 hours. Subjects are tracked by a computer system, with data output approximately every second. Acute preference was calculated from the archived data as the mean temperature that the fish occupied during the first two hours of dynamic experimentation. Acute preference measurements were used to determine final temperature preferendum and avoidance temperatures were used to determine behavioral tolerance. Critical thermal methodology (CTM) determined the CTmin and CTmax of the lionfish with loss of equilibrium (LOE) as the endpoint. It is assumed that beyond this temperature, the fish would be unable to survive. Temperature was increased or decreased by 0.33°C per minute until the end point was reached. Thermal tolerance polygons provide a visual representation of the lower and upper thermal avoidance temperatures, delineating the thermal range of the species. Their CTmin and CTmax (acclimated to 25°C) were compared experimentally with two other Florida reef fish species (Cephalopholis cruentata and Lutjanus apodus). Acute preferences of juvenile invasive lionfish showed a final preferendum at 28.7 ± 1°C, but with no significant difference between acclimation temperatures. The thermal tolerance polygon of invasive lionfish shows a strong correlation between CTM and acclimation temperature, with the highest CTmax at 39.5°C and the lowest CTmin at 9.5°C. The thermal polygon, preference, and avoidance data describes the thermal niche of the lionfish. Lionfish CTM (24.61°C) is narrower than those of C. cruentata (25.25°C) and L. apodus (26.87°C).